The Analysis of Financial Ratio in PT Telkom Indonesia Tbk on 2020-2022 - Amar Hidayatullah; Maulana Rizki; Rizky Afanin Syahrani; Samuel Barita Silalahi; Sabda Dian Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the financial statements of PT. Telkom Indonesia (Persero) Tbk for the period 2020 to 2022. It employs a descriptive quantitative research approach. The data collection method used is documentation, and the data analysis method consists of financial ratio analysis including liquidity ratios, solvency ratios, activity ratios, and profitability ratios for the years 2020 to 2022. The analysis results indicate that PT. Telkom Indonesia's financial ratios during the studied period demonstrate good performance. The liquidity ratios show the company's ability to meet short-term obligations, while profitability ratios indicate the company's capacity to generate satisfactory profits. The solvency ratios reveal the company's capability to fulfill long-term obligations. Overall, the analysis demonstrates that PT. Telkom Indonesia's financial performance for 2020-2022 is good and stable, providing valuable information for stakeholders to make informed decisions.